Sensory Testing Method, Third Edition - Wolf, Mona B. (Journal of ASTM International. Manual Series ;, 2020)
Manual 26 gives the reader a general knowledge of sensory evaluation methods. It provides a base of practical techniques and the controls that are necessary to conduct simple sensory studies.